COMPARATIVE STUDY CATCHING BUSINESS BETWEEN FISHING CATCH AMBAI AND PENGERIH IN THE VILLAGE MESKOM SUBSDISTRICT BENGKALIS DISTRICT BENGKALIS RIAU PROVINCE - Zikri Fahmi; Eni Yulinda; Ridar Hendri (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Study was conducted in July and August 2016 in the village Meskom subsdistrict Bengkalis district Bengkalis Riau Province.This study aims to know the investment, the gross income, net income ,and feasibility business between a fishing catch Ambai and Pengerih in the village Meskom subsdistrict Bengkalis district Bengkalis. Business investment a fishing catch Ambai less than Pengerih, where business investment Ambai Rp 17.290.000,- (5 bags) and Rp 21.002.500,- (7 bags), business investment with a fishing catch Pengerih Rp 18.812.000,- (5 bags) and Rp 22.680.000,- (7 bags). Gross income and net income per year received Ambai business less than Pengerih, when the income gross and net Ambai business 5 bags Rp 74.949.000,- and Rp 54.549.000,- then 7 bags Rp 109.869.000,- and Rp 87.939.000,- while business pengerih 5 bags Rp 100.501.000,- and Rp 75.834.000,- then 7 bags Rp 134.961.000,- and Rp 111.469.000,-. Based on analysis of the feasibility study conducted shows that effort arrest used a fishing catch Pengerih deserve developed than a fishing catch Ambai.Keywords: Ambai, Pengerih, Meskom Village, Feasibility Analysis